Paulinus of Nola and Augustine on the power of images Paulinus von Nola und Augustinus über die Macht der Bilder - Köckert, Charlotte (Zeitschrift für Theologie und Kirche, 2024)
This article examines reflections on the effect and use of images in churches by Paulinus of Nola and Augustine of Hippo. It reconstructs the outlines of an early Christian theory of images based on a complex interplay between images and texts. It is argued that Paulinus and Augustine share fundamental assumptions about images but evaluate them differently due to their different social roles and philosophical influences. Paulinus ascribes to visual media and material objects a power comparable to speech in bringing people to faith and emphasises the psychological and didactic potential of material images, especially for the uneducated. Augustine stresses the complex preconditions for the reception of images on the part of the viewer and therefore takes a more critical stance towards their use as a medium for instructing the uneducated. While he advocates strict regulation of the use of images, he does not rule out their use in churches as, for example, Epiphanius of Salamis did.
CRIS-Team Scopus Importer:2025-02-04